2012
DOI: 10.17221/96/2012-agricecon
|View full text |Cite
|
Sign up to set email alerts
|

Changes of the varietal structure of vineyards in the Czech Republic

Abstract: Th e paper describes changes in the structure of varieties grown in the Czech Republic. Th e authors examine the development taking place in this domain within the last 14 years (i.e. from 1997 to 2010). Th e paper analyses the reasons of these changes and tries to describe the future development expected after 2010. Th e article also examines the cost and profi tability of growing grapes and wine prices. Th e current production potential of the Czech Republic is 19 633.45 hectares of vineyards. As compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…The realignment totally took place at the end of the decade (Anderson and Nelgen 2011). Chládková et al (2012) found that the major innovative element of the impact on the economy of the wine is the application of the European legislation for the common wine market. Concerning the Czech wine industry, a significant increase of the grape varieties was observable and they found that the profitability of the sector highly depends on the domestic consumption and the cultivation of grapes with the emphasis on the quality improvement.…”
mentioning
confidence: 99%
“…The realignment totally took place at the end of the decade (Anderson and Nelgen 2011). Chládková et al (2012) found that the major innovative element of the impact on the economy of the wine is the application of the European legislation for the common wine market. Concerning the Czech wine industry, a significant increase of the grape varieties was observable and they found that the profitability of the sector highly depends on the domestic consumption and the cultivation of grapes with the emphasis on the quality improvement.…”
mentioning
confidence: 99%